An improved shear modified GTN model for ductile fracture of aluminium alloys under different stress states and its parameters identification. (15th February 2021) - He, Zao; Zhu, Hao; Hu, Yumei
Highlights: An improved shear modified GTN model is proposed for ductile fracture prediction of materials under different stress states; The damage parameters are calibrated using a FE inverse calibration method incorporating the Latin hypercube design, Kriging approximate model and NLPQL optimization method; Influence of each damage parameter on damage evolution under different stress states is analyzed by a unit cell model; Reasonable identification results are obtained for the aluminum alloy 6061 using the proposed method; The mechanism of deformation and failure are studied using fracture morphology analyses and damage analyses using FE simulation in microscale and macroscale perspectives. Graphical abstract: Image, graphical abstract Abstract: To solve the problem that the original GTN model cannot accurately simulate ductile fracture of material under low stress triaxiality, many scholars have made shear improvement to it, but these shear modified GTN models have their own advantages and disadvantages and the parameters are difficult to be determined. An improved shear modified GTN (ISMGTN) model containing two independent damage mechanisms is proposed for ductile fracture prediction of materials under different stress states. The shear damage parameters, tensile damage parameters and the hardening parameters are identified using a FE inverse identification method incorporating the Latin hypercube design, Kriging approximate model and NLPQL optimization method performed in the optimization software ISIGHT. Influence of each damage parameter on damage evolution under different stress states is analyzed by a unit cell model. Accuracy of the ISMGTN model and feasibility of the damage parameters identification method are verified by performing them on a material aluminum alloy 6061 with 0°, 30° and 60° shear tests, plate tensile tests, and notched tensile tests. Additionally, fracture morphology analyses of the fractured specimen and contour plots of the effective tensile damage and effective shear damage from the FE analysis using the identified parameters are performed to study possible mechanism of deformation and failure in microscale and macroscale perspectives, respectively, and a good consistence is obtained.